2021
DOI: 10.11591/ijere.v10i3.20502
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lesson study on mathematics anxiety and mathematics achievement of Malaysian foundation programme students

Abstract: <p>Based on many researches, there is negative relationship between mathematics anxiety and achievement. However, there is no study about mathematics anxiety and achievement in Malaysian foundation centers. This research studied the impact of Lesson Study (LS) on mathematics anxiety and achievement of students in a Malaysian university. A total of eight lecturers were involved in planning the LS which was experimented on 44 students as experimental group, while 42 others were in the control group. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…3 (25%) of the 12 papers reviewed in this study argued that adopting a problem-based teaching style is not enough to reduce Mathematics anxiety, the papers stated that a problem-solving teaching style will reduce anxiety in students. Gholami [50] used Mathematics Anxiety Scale-Revised to measure students' Mathematics anxiety with 86 students grouped into an experimental group and a control group. The study found that there is a detrimental correlation between students' Mathematics anxiety and teaching methods [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 (25%) of the 12 papers reviewed in this study argued that adopting a problem-based teaching style is not enough to reduce Mathematics anxiety, the papers stated that a problem-solving teaching style will reduce anxiety in students. Gholami [50] used Mathematics Anxiety Scale-Revised to measure students' Mathematics anxiety with 86 students grouped into an experimental group and a control group. The study found that there is a detrimental correlation between students' Mathematics anxiety and teaching methods [50].…”
Section: Resultsmentioning
confidence: 99%
“…Gholami [50] used Mathematics Anxiety Scale-Revised to measure students' Mathematics anxiety with 86 students grouped into an experimental group and a control group. The study found that there is a detrimental correlation between students' Mathematics anxiety and teaching methods [50]. Students in the experimental group used a student-centered approach to tackle problems both individually and in groups.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, participants' age ranged between 18 and 23 (see Table 2). Participants were college students [52,53,54], foundation programs students [32], or were enrolled in university courses and majors such as business [35], calculus [36], elementary education [34,38], geoscience [51], nursing [33] and psychology [37,55], and they were attending mathematics classes when the studies were conducted.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The available interventions differ in sample characteristics, intervention approach, program duration, and the assessment adopted. For example, participants were selected from college students [32], nursing students [33], and preservice elementary teachers [34], just to mention a few. Intervention duration ranged from single-session interventions [35] to multiple-session interventions over six months [36], while interventions spanned from relaxation techniques such as listening to music [37] to improvements in teaching mathematics [32], to clinical psychological interventions [38].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have used primarily a quantitative approach to explore mathematics anxiety [28], [34]- [37]. More current researches [38]- [40] have sought the relationships between mathematics anxiety and other variables such as gender, mathematics self-efficacy and mathematical literacy. However, these researches still gathered data through a quantitative approach and have viewed them in terms of the manifestation of mathematics anxiety as opposed to sources of mathematics anxiety.…”
Section: Problem Statement and Research Objectivesmentioning
confidence: 99%